Aquatic Plants of Jait Sagar Lake, Bundi; South-East Rajasthan - O.P.SHARMA (International Journal of Pharma and Bio Sciences, 2018)
Floristic study is a powerful tool in plant systematics. The present paper highlights comprehensive aquatic vegetation of Jait Sagar lake of Bundi district, a biodiversity rich area of south-east Rajasthan. Aquatic plants were found to be important for the survival of fauna, and they have potential for strong ecosystem. Lake ecosystem suffers considerable degradation and destruction due to natural and anthropogenic causes. This study might be useful to supplement information with regard to its species diversity observation. Studies have been conducted by extensive survey in and around the area between 2014 and 2016. The result presented in this paper are based on two years of exploration and studies of aquatic flora of this lake. In the present study 30 angiospermic species included 26 genera and 19 families and 02 pteridophytic species occurring in this lake have been observed and recorded. Status of the important aquatic plants of this lake has been mentioned in this paper. The Main aquatic genera of the study area belong to the families of Alismataceae, Ceratophyllaceae, Hydrocharitaceae, Lemnaceae,Najadaceae and Potamogetonaceae. Fern aquatic genera belong to the families of Salviniaceae and Marsileaceae. This study reveales that the major problem that the lake faces are habitat destruction and eutrophication. Due to decrease in habitat area and consumeristic culture of human beings, a number of aquatic species is decreasing rapidly. This study deals with floristic analysis of this lake and it is an attempt to inspire societies to conserve the habitat and its flora.